2018
DOI: 10.1159/000488150
|View full text |Cite
|
Sign up to set email alerts
|

Asleep Deep Brain Stimulation Reduces Incidence of Intracranial Air during Electrode Implantation

Abstract: Background: Asleep deep brain stimulation (aDBS) implantation replaces microelectrode recording for image-guided implantation, shortening the operative time and reducing cerebrospinal fluid egress. This may decrease pneumocephalus, thus decreasing brain shift during implantation. Objective: To compare the incidence and volume of pneumocephalus during awake (wkDBS) and aDBS procedures. Methods: A retrospective review of bilateral DBS cases performed at Oregon Health & Science University from 2009 to 2017 was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Recent studies 15,17,23,24 have demonstrated that the incidence of intracerebral hemorrhages, infections, and epilepsy were similar between asleep and awake DBS surgery, which is generally consistent with our results. In this study, the volume of intracranial air was significantly lower in the GA group than that in the LA group, which is consistent with previous reports 17,25 . Awake DBS resulted in significantly larger cortical brain shifts 25 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recent studies 15,17,23,24 have demonstrated that the incidence of intracerebral hemorrhages, infections, and epilepsy were similar between asleep and awake DBS surgery, which is generally consistent with our results. In this study, the volume of intracranial air was significantly lower in the GA group than that in the LA group, which is consistent with previous reports 17,25 . Awake DBS resulted in significantly larger cortical brain shifts 25 .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the volume of intracranial air was significantly lower in the GA group than that in the LA group, which is consistent with previous reports 17,25 . Awake DBS resulted in significantly larger cortical brain shifts 25 . Additionally, awake DBS surgery has the disadvantage of potential local anesthetic drug allergies 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Successful clinical results on the intraoperative imaging to verify the accuracy of STN lead position instead of electrophysiological structure mapping or stimulation tests during DBS surgery have been reported [23,29,31,37,[40][41][42][43][44]. In recent studies on the advancement of intraoperative imaging, no significant clinical results were found when compared to awake DBS [16,30,37,45,46].…”
Section: Using Intraoperative Imagingmentioning
confidence: 99%
“…Factors such as intraoperative CSF leakage, degree of pneumocephalus, body position, burr hole sealing, and number of punctures have been investigated as causes of lead position accuracy. 14) However, the resolution of the O-arm makes it difficult to confirm brain parenchyma misalignment intraoperatively. Reduction of pneumocephalus during sedated DBS can improve the accuracy of electrode position, and the use of intraoperative imaging remains a potential way to identify and improve the accuracy of intraoperative pneumocephalus.…”
Section: Accuracymentioning
confidence: 99%